THE RELATIONSHIP OF AGE AND EDUCATION ON KNOWLEDGE ABOUT ANEMIA IN PREGNANT WOMEN AT TOROH COMMUNITY HEALTH CENTER 1 - Wahyu Dewi Hapsari; Sri Martini (Jurnal Profesi Bidan Indonesia, 2024)
Background Anemic pregnant women experience a condition where their red blood cells do not meet their body's physiological needs. This can have an impact on increasing fetal morbidity and mortality rates as well as increasing the risk of low birth weight in babies. Cases of anemia in pregnant women in the 1st trimester were found to increase from 75 to 108 in January – August 2023 at the Toroh Community Health Center 1, Grobogan Regency. Purpose: To determine the relationship between age and education on knowledge about anemia in pregnant women at the Toroh Community Health Center 1. Method: Using analytical survey research methods with a cross sectional plan with nonrandom sampling techniques so that the total sample is 30 pregnant women. Results Univariate analysis showed that the majority of respondents were aged 20-35 years, 26 people (86.7%), 14 people had junior high school education (46.7%), 23 people had less knowledge (23%) and 18 people were anemic pregnant women (60%). Bivariate analysis with the chi-square test showed that there was a relationship between age and pregnant women's knowledge about anemia (p value 0.015 < 0.05), and there was no relationship between education and pregnant women's knowledge about anemia (p value 0.139 > 0.05). Conclusion: There is a relationship between age and pregnant women's knowledge about anemia (p value = 0.016) and there is no relationship between education and pregnant women's knowledge about anemia (p value = 0.139) at Toroh Community Health Center 1